How to Promote the Agricultural Company Through Environmental Social Responsibility to Achieve Sustainable Production? - Huang, Stanley Y. B.; Yu, Chun-Chieh; Lee, Yue-Shi (Frontiers in Environmental Science, 2022)
This survey employs the multi-level growth curve model to demonstrate how to promote the development of the company’s environmental innovation in agricultural companies specializing in the agricultural production and export of agricultural products to achieve sustainable production through environmental social responsibility and environmental engagement according to the engagement theory. The empirical data is collected by 70 chief executive officers (CEO) and their 210 supervisors of top management teams (TMT) of Taiwanese agricultural companies in six months. The empirical results demonstrate that environmental social responsibility significantly influences the TMT’s environmental engagement development, which in turn significantly influences the agricultural company’s environmental innovation. These empirical results can not only promote the sustainable production literature in the agricultural field but also help these agricultural companies implement environmental innovation to realize sustainable production of agricultural exports.